THE DETERMINANT OF RISK MANAGEMENT DISCLOSURE - Ardianingsih, Arum; Aminatuzzuhro; Sholehah, Hikma Markatus (Universitas Kristen Krida Wacana, 2025)
Risk disclosure provides information about risks that can be used as considerations in making economic decisions. The purpose of this study is to understand the characteristics of the board of directors and management ownership impact on managed risk disclosure. The object of the study is banking companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022 The research data was taken from banking annual reports. The population is 41 banking companies, and the sample used is 39 companies. The study uses a total of 195 research data. The sampling technique uses purposive sampling. The analysis technique used in this study is Partial Least Square (PLS) - Structural Equation Modeling (SEM) with WarpPLS 8.0 software. The results of the study are that the size of the board of directors has a positive effect on risk management disclosure, board duality has no effect on risk management disclosure. Then the study also provides empirical evidence that managerial ownership has a significant negative effect on risk management disclosure. Keywords: Board of Directors, Disclosure, Risk, Ownership